CLINICAL CHARACTERISTICS AND LABORATORY RESULTS OF A PREGNANT WOMAN WITH SARS-COV-2 INFECTION - Banasevic, Marijana (HEALTH CARE, 2022)
Introduction/aim: The most common symptoms and laboratory signs of SARS-CoV-2 infection in pregnancy are the following: fever, cough, dyspnea, diarrhea, lymphocytopenia, leukocytosis and a high level of CRP. However, pregnant women with comorbidities are at an increased risk of severe forms of Covid-19. Numerous studies point to the fact that pregnant women with the confirmed SARS-CoV-2 infection have more than two times higher risk of preterm labor, and that they are at an increased risk of preeclampsia and emergency Cesarean section. The aim of this paper is to analyze the course and outcome of SARS-CoV-2 confirmed in a young woman in the 39th week of pregnancy. Case report: A pregnant woman with the confirmed SARS-CoV-2 infection in the 39th week of pregnancy delivered a baby on the sixth day from the appearance of symptoms and signs of disease. At the beginning of infection, the patient reported fever, poor general health status, and then cough and chest pain. The infection was accompanied by increased levels of C reactive protein, D-dimer and lymphocytopenia. The patient is a young woman without comorbidities, but pneumonia with a tendency toward progression was diagnosed six days after symptoms and signs appeared, due to which her hospitalization after delivery was prolonged. The findings of computerized tomography showed bilateral interstitial Covid-19 pneumonia. The patient was hemodinamically stable all the time during hospitalization and did not need oxygen support. The baby was delivered vaginally with good general health status (Apgar score 9/10, body weight). SARS-CoV-2 infection was not confirmed with the rapid antigen test in the newborn. Conclusion: Further research is needed in this field, especially research on the course and outcome of infection in pregnant women during the first and second trimester of pregnancy, as well as on the ways how to reduce unwanted neonatal outcomes in pregnant women with SARS-CoV-2 infection.